Photometry and spectroscopy of GRB 060526: a detailed study of the afterglow and host galaxy of a z = 3.2 gamma-ray burst - Thone, C.; Kann, D.; Johannesson, G.; Selj, J.; Jaunsen, A.; Fynbo, J.; Akerlof, C.; Baliyan, K.; Bartolini, C.; Bikmaev, I.; Bloom, J.; Burenin, R.; et al. (EDP Sciences, 2010)
Aims. With this paper we want to investigate the highly variable afterglow light curve and environment of gamma-ray burst (GRB) 060526 atz = 3.221.Methods. We present one of the largest photometric datasets ever obtained for a GRB afterglow, consisting of multi-color photometric data fromthe ultraviolet to the near infrared. The data set contains 412 data points in total to which we add additional data from the literature. Furthermore,we present low-resolution high signal-to-noise spectra of the afterglow. The afterglow light curve is modeled with both an analytical model usingbroken power law fits and with a broad-band numerical model which includes energy injections. The absorption lines detected in the spectra areused to derive column densities using a multi-ion single-component curve-of-growth analysis from which we derive the metallicity of the host ofGRB 060526.Results. The temporal behaviour of the afterglow follows a double broken power law with breaks at t = 0.090± 0.005 and t = 2.401± 0.061 days.It shows deviations from the smooth set of power laws that can be modeled by additional energy injections from the central engine, although somesignificant microvariability remains. The broadband spectral-energy distribution of the afterglow shows no significant extinction along the line ofsight. The metallicity derived from S ii and Fe ii of [S/H] = –0.57±0.25 and [Fe/H] = –1.09±0.24 is relatively high for a galaxy at that redshift butcomparable to the metallicity of other GRB hosts at similar redshifts. At the position of the afterglow, no host is detected to F775W(AB) = 28.5 magwith the HST, implying an absolute magnitude of the host M(1500 Å) > –18.3 mag which is fainter than most long-duration hosts, although theGRB may be associated with a faint galaxy at a distance of 11 kpc.